2010
DOI: 10.1111/j.1365-2133.2010.09741.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mutation screening of KRT5 supports the hypothesis that Galli-Galli disease is a variant of Dowling-Degos disease

Abstract: We found further evidence to suggest that GGD is indeed a variant of DDD and not a distinct disease entity. Two facts in particular support this conclusion: the same KRT5 mutation was found in patients with GGD and in patients with DDD, and acantholysis seems to be present in a large number of patients who had previously been assigned a diagnosis of DDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 11 publications
(30 reference statements)
0
57
0
7
Order By: Relevance
“…The clinical presentation and the genetic backgrounds of these individuals indicated that GGD is a variant of DDD and not a distinct disease entity. 6,10,11 Another locus for DDD was identified in an affected Chinese family; this locus is on chromosome 17p13.3, but the responsible mutation has not been identified to date. 12 Additionally, recent studies of two Chinese families with DDD led to the identification of mutations in POFUT1 (MIM 607491), which encodes protein O-fucosyltransferase 1 from the Notch pathway.…”
Section: Dowling-degos Disease (Ddd [Mim 179850 Mim 615327])mentioning
confidence: 98%
See 1 more Smart Citation
“…The clinical presentation and the genetic backgrounds of these individuals indicated that GGD is a variant of DDD and not a distinct disease entity. 6,10,11 Another locus for DDD was identified in an affected Chinese family; this locus is on chromosome 17p13.3, but the responsible mutation has not been identified to date. 12 Additionally, recent studies of two Chinese families with DDD led to the identification of mutations in POFUT1 (MIM 607491), which encodes protein O-fucosyltransferase 1 from the Notch pathway.…”
Section: Dowling-degos Disease (Ddd [Mim 179850 Mim 615327])mentioning
confidence: 98%
“…[5][6][7][8] In subsequent years, we screened more than 40 individuals with DDD and found KRT5 mutations in fewer than 50%, with only 16 simplex and familial cases. 9,10 Thus, the causes of a large number of unsolved cases of DDD remain to be explained. In some individuals with DDD, who had originally been diagnosed with Galli-Galli disease (GGD), the additional histopathological feature of acantholysis was observed.…”
Section: Dowling-degos Disease (Ddd [Mim 179850 Mim 615327])mentioning
confidence: 99%
“…In light of substantial clinical, histological and mutational overlap between GGD and DDD, they are considered to belong to the same entity 2, 3. Mutations in KRT5 (encoding keratin 5) have been associated with GGD/DDD since 2006 2, 3, 4, 5.…”
mentioning
confidence: 99%
“…4 These findings indicate that GGD is not a distinct disease, but rather a variant of DDD predisposing to acantholysis. The missense mutation c.418dupA, which is the most common mutation identified for DDD/GGD, leads to a premature stop codon and consequently a truncated KRT5.…”
Section: Galli-galli Disease Is An Acantholytic Variant Of Dowling-dementioning
confidence: 95%